Alternative Solution on the Execution of Court’s Verdict within Employment Termination Dispute - Budi Santoso (Universitas Airlangga, 2018)
This paper aims to analyze the juridical barriers of execution of verdict in case of dismissal dispute as well as offering a solution to the execution of such verdict to be carried out so that workers obtain their rights. Through the statute and case approaches, it is concluded that the juridical barriers are: 1) in a reminder implementation, the existing regulation does not authorize the bailiff to force the defendant to attend the reminder call if the defendant refuses to attend the call voluntarily; and 2) in the execution seizure, the goods to be confiscated shall belong to the defendant, whereas the plaintiff can not prove it because all the evidence is in the hands of the employer. While alternative solutions in order the verdict may be executed well are: 1) involving authorized third parties who may assist the worker as a plaintiff to prove the ownership of the items for which the request is for confiscation; and 2) implementing the body’s forced effort to an employer with a bad faith in accordance with Supreme Court Regulation No. 1 Year 2000, but by reducing the minimum limit of debt that is not as much as one billion rupiah due to cases of dismssal dispute are less possibility of paying for the workers’ rights who reached that amount.